A Randomized Clinical Trial to Compare a Precision Nutrition Intervention Targeting a Reduction in Postprandial Glycemic Response to Meals With a Low-Fat Diet for Weight Loss. (14th June 2022) - Popp, Collin; Hu, Lu; Wang, Chan; Curran, Margaret; Li, Huilin; Kharmats, Anna; Thomas, Lauren; Pompeii, Mary Lou; Mottern, Meredith; Polyn, Antonia; Schoenthaler, Antoinette; St-Jules, David; et al.
Abstract: Objectives: The primary aim is to compare the effects of a low-fat diet vs a personalized diet on % weight loss at 6-months. Secondary outcomes include body composition (fat mass [FM] and fat free mass [FFM]), resting energy expenditure (REE) and adaptive thermogenesis (AT). Methods: The Personal Diet Study was a 6-month, single-center, randomized clinical trial in adults with pre-diabetes and moderately controlled type 2 diabetes who were overweight or obese. Participants were randomized to follow either a hypocaloric low-fat diet, with < 25% energy intake from total fat ( Standardized ), or a hypocaloric personalized diet determined by a machine learning algorithm which predicts PPGR to meals ( Personalized ). Participants in both arms received behavioral counseling and logged dietary intake and physical activity into a smartphone app. Participants in the Personalized arm received real-time feedback as color-coded scores based on pre-consumed meals entered into the smartphone app. T-tests were used to assess group differences. Results: A total of 200 adults ( Standardized : n = 97 vs. Personalized : n = 103) contributed data (mean [SD]: age, 58 [11] years; 67% female; BMI, 34.0 [4.8] kg/m 2 ; HbA1c, 5.8 [0.6]%; Metformin use, 21.0%). There were no significant group differences in mean % weight loss ( Standardized : −4.4 [4.8]% vs Personalized : −3.3 [5.4]%; p = 0.19), mean absolute change in FM ( Standardized : −2.7 [3.4] kg vs. Personalized : −1.6 [3.5] kg; p = 0.18), and AT between the two arms ( Standardized : −54.7 [177] kcal/d vs. Personalized : 26.2 [199] kcal/d; p = 0.078). However, the Standardized arm lost significantly more FFM (−1.4 [1.6] kg vs. −0.45 [2.0] kg; p = 0.03) and had a greater decrease in REE (−111.0 [195.0] kcal/d vs. 1.93 [215.0] kcal/d; p = 0.02) compared to Personalized . Conclusions: A personalized diet to minimize PPGR had no greater effect on % weight loss compared to a low-fat diet at 6-months. Future precision nutrition trials may require deeper phenotyping of individuals or the development of body weight-specific algorithms. Funding Sources: Supported by grants from the American Heart Association 17SFRN33590133.